Indoor air pollution from biomass combustion and its adverse health effects in central India: An exposure-response study - Neelam D Sukhsohale; Uday W Narlawar; Mrunal S Phatak (Wolters Kluwer Medknow Publications, 2013)
Background: Some of the highest exposures to air pollutants in developing countries occur inside homes where biofuels are used for daily cooking. Inhalation of these pollutants may cause deleterious effects on health. Objectives: To assess the respiratory and other morbidities associated with use of various types of cooking fuels in rural area of Nagpur and to study the relationship between the duration of exposure (exposure index [EI]) and various morbidities. Materials and Methods: A total of 760 non-smoking, non-pregnant women aged 15 years and above (mean age 32.51 ΁ 14.90 years) exposed to domestic smoke from cooking fuels from an early age, working in poorly ventilated kitchen were selected and on examination presented with various health problems. Exposure was calculated as the average hours spent daily for cooking multiplied by the number of years. Symptoms were enquired by means of a standard questionnaire adopted from that of the British Medical Research Council. Lung function was assessed by the measurement of peak expiratory flow rate (PEFR). PEFR less than 80% of the predicted was considered as abnormal pulmonary function. Results and Conclusions: Symptoms like eye irritation, headache, and diminution of vision were found to be significantly higher in biomass users (P < 0.05). Abnormal pulmonary function, chronic bronchitis, and cataract in biomass users was significantly higher than other fuel users (P < 0.05). Moreover an increasing trend in prevalence of symptoms/morbid conditions was observed with increase in EI. The presence of respiratory symptoms/morbid conditions was associated with lower values of both observed and percent predicted PEFR (P < 0.05 to 0.001). Thus women exposed to biofuels smoke suffer more from health problems and respiratory illnesses when compared with other fuel users.